[Rezension von: Sacrifice and modern thought] - Matthiesen, Michon M. (The journal of theological studies, 2014)
Co-editor Zachhuber's comment that modern fascination with sacrifice rests on ‘precarious’ grounds—on the virtual non-existence of sacrifice as a ritual practice—haunts this provocative volume. The statement points to a truth well evidenced in this book, namely, that ‘sacrifice’ has migrated a good distance from a distinctly ritual context, involving the presentation and transference of a gift (hostia) into the realm of the sacred.